Pengaruh Sosial Media terhadap Peningkatan Kejahatan di Kalangan Remaja di Indonesia - Athaya Diah Dakota; Valensia Valensia (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to identify the impact of social media on the increase of crimes among teenagers in Indonesia. Crimes emerging alongside the growth of social media include cyberbullying, online fraud, pornography, and radicalization. The research employs a qualitative approach with a case study, gathering data through interviews with teenagers, parents, and experts in criminology and digital security. The findings indicate that teenagers who use social media more frequently are more vulnerable to negative behaviors and cybercrimes. The study also reveals that the lack of parental supervision and social media dependency are key factors contributing to the rise in crimes among teenagers. To address these issues, digital education, enhanced parental oversight, and stricter government regulations are necessary.